Energetic D+ and He+ impinging on solid beryllium: Observation of physical and chemically assisted atomic and molecular ion sputtering. (March 2022) - Duensing, Felix; Hechenberger, Faro; Ballauf, Lorenz; Reider, Anna Maria; Menzel, Alexander; Zappa, Fabio; Dittmar, Timo; Böhme, Diethard K.; Scheier, Paul
Highlights: Chemical assisted sputtering of deuterons colliding with a heated beryllium surface. Pure physical sputtering upon helium ion collisions with the same surface. Various ablated ions were analyzed by mass spectrometry. Adsorption of water to the surface leads to additional ablated ions. Analogous to impact of plasma deuterons on first wall in fusion devices. Abstract: Our Surface-Time-Of-Flight (SurfTOF) tandem mass spectrometer apparatus has been employed in a comparative investigation of ion sputtering induced by mono-energetic D + and He + ion beams impinging on a Be surface at 700 K with impact energies from 5 to 500 eV. Both chemically assisted sputtering (by D + impact below 50 eV) and physical sputtering (by He + and D + above 50 eV) were observed. Be + was the dominant sputtered ion at all energies. Chemically assisted sputtering mechanisms are proposed for the concomitant chemical sputtering of Be +, Be2 + and BeD + ions (by D + at low energies). Evidence was also obtained for the sputtering of BeO + and Be2 O + by both He + and D + impact ions (with a minimum at 30 eV with D + ), but only above 30 eV with He + . They are ascribed to the presence of BeO and Be2 O impurities in the surface layer of Be. Water molecules adsorbed on the Be sample gave rise to BeH + and BeOH + in the sputtered ion spectrum primarily at higher energies above 30 eV where Be + ejection is enhanced. Combined observations with a quartz crystal microbalance and a Faraday cup provided preliminary insight into the sputter yields of neutral and ionized beryllium. These results can be carried over to the erosion of Be by plasma deuterons, and T + by extension, in its use as the first wall for the ITER blanket in fusion technology.